One Village One Development: A Government Concept in The Development of The Tourism Sector in Batu City - Ratuloly, Rudy; Rifa’i , Muhamad; Hardianto, Willy Tri (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2023)
Tourism is an action or a movement produced by someone or something that goes from one location to another repeatedly for a while with the aim of enjoying the beauty of nature and without generating enough money to pay the cost. This study is expected to decide and break up the work of public authorities and the community in developing the travel industry in Batu City. This study uses an interesting subjective exploration. Determination of research informants are Tourism and Marketing Product Development Staff, Staff of Control Analysis and Reporting of development planners and staff of the Head of Planning. Data collection techniques are interviews, documentation, observation. Data analysis through the process of triangulation. Based on the results of this study, the role of the Batu City government has been very good in developing the existing tourism potential in the villages in Batu City itself because in terms of physical aspects, attractions, accessibility, activities and facilities as well as socio-economics have been very good and supportive for developing tourism where the government's role is carried out properly as carried out by the Tourism Office, the Bapplitbangda Service and the village government which is under the auspices of Batu City itself by carrying out tasks such as providing training to local communities and the Bapplitbangda Service providing good infrastructure facilities and village apparatus who develop existing excursions so that with good tourism development it can attract visitors to visit these vacation spots and greatly impact on increasing PAD by utilizing existing natural potential.